Political journeys : the open democracy essays - Halliday, Fred. (London, 2011)
Fred Halliday always combined the broad sweep of modern history, its currents and ideas with a profound knowledge of modern revolutions, the Middle East and national movements. This collection of columns written for openDemocracy between 2004 and 2009 is proof of a subtle worldview that continues to generate questions: what is the relation between religion, nationalism and progress? Is a new international order possible? When is intervention a force for progress? From the big headlines topics like the Iraq war or the Danish cartoons, to the unexpected comparisons, of Tibet and Palestine or Afghanistan and the Falklands, Halliday is a perennially surprising and enlightening guide to the major issues of international politics.
Keywords: World politics